1987
DOI: 10.2307/3053597
|View full text |Cite
|
Sign up to set email alerts
|

Participation and Flexibility in Informal Processes: Cautions from the Divorce Context

Abstract: Based on open-ended interviews with the parties and lawyers in twenty-five informally settled divorce cases, this study finds that the informal process is often contentious, adversarial, and beyond the perceived control of one or both parties. Although settlement in some cases reflects flexibility, party participation, and true agreement, in most cases it reflects unequal financial resources, procedural support, or emotional stamina. Parties report settling issues such as child support according to nonlegal, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 15 publications
2
27
0
Order By: Relevance
“…Similarly, there is a pervasive element of coordination in the kind of disputes and negotiations more typically studied by lawand-society scholars (e.g., Macaulay 1963;Erlanger et al 1987;Edelman et al 1993). All that is necessary (among other possibilities) is that the parties involved in a dispute jointly regard some outcome as the worst result.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Similarly, there is a pervasive element of coordination in the kind of disputes and negotiations more typically studied by lawand-society scholars (e.g., Macaulay 1963;Erlanger et al 1987;Edelman et al 1993). All that is necessary (among other possibilities) is that the parties involved in a dispute jointly regard some outcome as the worst result.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…It additionally implies a comparison with informal negotiations in other legal arenas, including civil cases such as divorce (see, e.g., Erlanger et al, 1987;Mnookin and Kornhauser, 1979). This means studying narratives in different plea bargaining settings, such as those involving felony offenses.…”
Section: Discussionmentioning
confidence: 99%
“…Kagan (2001), Galanter and Cahill (1994) and Erlanger et al (1987) maintain that uncertainty about the outcome of court cases is related to a greater propensity to settle, and a number of observers (e.g., Emery, 1994;Garfield, 2002) have suggested that one of the reasons clients want mediation is the unpredictability of litigated outcomes. However, Hunter (2003) has pointed out that settlement in family law is the norm despite the fact that judicial outcomes are considered highly predictable in the Australian setting she studied.…”
Section: Predictability Of Outcomementioning
confidence: 97%
“…It has also been said that a belief in the unpredictability of judicial decisions makes settling a more attractive option (e.g., Galanter and Cahill, 1994;Erlanger et al, 1987). In order to examine the relationship between the view of judicial decision-making as unpredictable, and adversarial attitudes and behaviors, each of the respondents was asked to indicate to what extent they could predict the outcome of court decisions on the various issues involved in divorce (on a scale of 1-very predictable-to 5-very unpredictable).…”
Section: Predictability Of Litigated Outcomesmentioning
confidence: 99%